Feminism and the Islamic Revival: Freedom as a Practice of Belonging. (6th December 2012) - Weir, Allison
<x xml:space="preserve">Abstract</x> In her book, Politics of Piety: The Islamic Revival and the Feminist Subject, Saba Mahmood analyzes the practices of the women in the mosque movement in Cairo, Egypt. Mahmood argues that in order to recognize the participants as agents, we need to question the assumption that agency entails resistance to norms; moreover, we need to question the feminist allegiance to an unquestioned ideal of freedom. In this paper, I argue that rather than giving up the ideal of freedom, we can explore the possibility that there are different conceptions of freedom, and that the agency of the women in the mosque movement can be understood through a conception of freedom as a practice of connection, or belonging. I develop this alternative paradigm through discussions of four conceptions of freedom: Foucault's theory of agency as self‐creation, positive freedom, communitarian freedom, and freedom as resistance.